2014
DOI: 10.1071/ch14172
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances Using Guanidinate Ligands for Chemical Vapour Deposition (CVD) and Atomic Layer Deposition (ALD) Applications

Abstract: Volatile metal complexes are important for chemical vapour deposition (CVD) and atomic layer deposition (ALD) to deliver metal components to growing thin films. Compounds that are thermally stable enough to volatilize but that can also react with a specific substrate are uncommon and remain unknown for many metal centres. Guanidinate ligands, as discussed in this review, have proven their utility for CVD and ALD precursors for a broad range of metal centres. Guanidinate complexes have been used to deposit meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 36 publications
0
24
0
Order By: Relevance
“…2H + + 2e À -H 2 (5) Photocatalysts are sought to be used in this process, which must be suitable for large-scale application. Whilst many transition metal oxides are known, their band gaps (B3 eV) tend to be too large (for visible light irradiation) and as such many bismuth oxide systems, amongst some other materials have received recent attention in the literature, since the ideal band gap for a photoelectrochemical (PEC) material would be 2 eV.…”
Section: Main Group Photoelectrochemical and Photocatalytic Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…2H + + 2e À -H 2 (5) Photocatalysts are sought to be used in this process, which must be suitable for large-scale application. Whilst many transition metal oxides are known, their band gaps (B3 eV) tend to be too large (for visible light irradiation) and as such many bismuth oxide systems, amongst some other materials have received recent attention in the literature, since the ideal band gap for a photoelectrochemical (PEC) material would be 2 eV.…”
Section: Main Group Photoelectrochemical and Photocatalytic Materialsmentioning
confidence: 99%
“…The most common method to thin films is CVD, which can be used to deposit on small scale coatings, such as microelectronics and larger areas of growth, for example glass/steel coatings. [3][4][5] The formation of thin films via AACVD is the result of homogeneous or heterogeneous reaction or a combination of both homogeneous nucleation in the gas phase and heterogeneous growth on the substrates. However, both the composition and structure of the deposited materials can be significantly effected by the nature and purity of the precursors.…”
Section: Introductionmentioning
confidence: 99%
“…Metal complexes of N ‐susbstituted guanidinates have been widely studied in the past due to their relevance in the fields of inorganic, organometallic, and materials chemistry , . Additionally, these complexes have been invoked as intermediates in metal catalyzed guanylation of amines with carbodiimides for guanidine synthesis .…”
Section: Introductionmentioning
confidence: 99%
“…for olefin polymerization and hydroamination reactions, [11][12][13][14][15] whereas certain alkyl-substituted complexes are sufficiently volatile to be useful precursors for ALD (atomic layer deposition) and CVD (chemical vapor deposition) processes. [16][17][18][19][20][21][22][23][24] Recent contributions to this field clearly revealed that the use of unsymmetrically substituted amidinate and guanidinates ligands leads to further improved volatility of the respective transition metal and lanthanide complexes. For example, replacement of the chelating guanidinate ligand in the tantalum(V) tetraamide precursor Ta(NMe 2 ) 4 [Me 2 NC(NiPr) 2 ] by the asymmetric ligand [Me 2 NC(NEt)(NtBu)]led to the significantly more volatile isomer Ta(NMe 2 ) 4 [Me 2 NC(NEt) (NtBu)].…”
Section: Introductionmentioning
confidence: 99%